Known facts: iron deficiency in Indonesia - Manikam, Nurul Ratna Mutu (Indonesian Nutrition Association, 2021)
More than half cases of anemia are due to iron deficiency. Anemia is a major and global public health problem that affects maternal and child mortality, child cognitive development and eventually productivity. Infancy, adolescence, and pregnancy are particularly at risk. Indonesia is a low middle country with the prevalence of anemia as high as 48.9% in pregnant women and 38.5% in children under 5 years old. It is even higher among adolescents aged 12-18 years, especially in rural areas. Low income and level of education seem to also contribute to iron deficiency. Indonesia government aims to prevent anemia in young and pregnant women by providing iron pills. Still, the etiology of anemia in Indonesia is various and many elements are preventing Indonesia women to consume pills and/or iron-rich foods. We aim to review the prevalence, risk factors associated with iron deficiency especially among women of reproductive age in Indonesia, including the socio-determinant influence on iron deficiency. We will also discuss the management of iron deficiency in Indonesia in comparison with international guideline to identify the potential gaps.